If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -2 = 3(x + 1) Reorder the terms: -2 + y = 3(x + 1) Reorder the terms: -2 + y = 3(1 + x) -2 + y = (1 * 3 + x * 3) -2 + y = (3 + 3x) Solving -2 + y = 3 + 3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + y = 3 + 2 + 3x Combine like terms: -2 + 2 = 0 0 + y = 3 + 2 + 3x y = 3 + 2 + 3x Combine like terms: 3 + 2 = 5 y = 5 + 3x Simplifying y = 5 + 3x
| 15/45=x/12 | | x^2-20x-98=0 | | 9b+4=2b+46 | | 25r^3-16r=0 | | 25r^3-16r=0 | | 11-8x=7x+17 | | 139-5x=3x-19 | | 2(x+6)=3(x-4)+5 | | q-7/4=3 | | v/11=5/3 | | -42-2x=6-6x | | 7-9x=7x+18 | | (7x^3+4x)(x^2+2)= | | 4(x-3)=23-x | | 9(2+x)=63 | | 4x+13=94 | | 2(3-5+7)+6= | | 5(14-x)=60 | | 8(x+1)=48 | | 3x(3+5)=24 | | -32=4(x+3) | | (2x+4y)+(4x+7y)=180 | | -3x^2+21x=15 | | 5x+5+4x+5+35=180 | | 1=-.5(3k-4) | | 3.50x=84 | | (3+3.50)x=84 | | 5m^2+2=47 | | -2/3q+2q=6/5q+12/5 | | 2[(12+2x)+(15+2x)]=74 | | 8y^2-23y-3= | | (-762.46)=h-32.061 |